Peran Kepala Sekolah Dalam Meningkatkan Kinerja Guru Pada Pembelajaran Online di SD Negeri Sidoarjo - M. Shodiq; Siti Maimunah (Departement of Mathematics Education, 2023)
The background of this research stems from the interest of researcher in the Covid-19 pandemic which has an impact on all sectors. One of them is the field of education which has an impact on the changes in learning method from face-to-face to online learning, thus educational services must adapt to those changes and students are required to study from home.The principal is a leader who has duties and responsibilities at school and plays important roles to improve teacher performance. The research method uses a qualitative descriptive approach to describe and analyze the roles of the principal in improving teacher performance in online learning at SDN Sidoarjo. Data collection techniques used in this study were observation, documentation, and in-depth interviews.Based on the results of the study, it was found that several indicators have been implemented by the principal, as follows: a) The school provides internet facility and the principal has instructed the teachers to apply online learning; b) The teacher showed good performance at SD Negeri Sidoarjo by carrying out online learning optimally; c) The principal has given motivation to the teachers through intensive coaching; d) The inhibiting factor for online learning is poor internet signal. Another factor is that both parents of the students are workers so that the assignments given by the teacher to students cannot be completed on time.The conclusion of this study is that although there are obstacles in online learning, the principal as a top leader provides online learning facilities and organizes training for teachers so that they can carry out online learning.